Repositioning the Value of Pancasila Justice in Debtor Protection in the Execution of Separatist Creditors - Raynaldi, Muhammad Ferdyanto (TABELLIUS: Journal of Law, 2023)
The implementation of executions by separatist creditors without going through court proceedings as regulated in Article 55 and Article 56 of Law Number 37 of 2004 is contrary to Pancasila justice. The method used is the normative juridical method. Based on the data obtained, it appears that the implementation of bankruptcy execution as regulated in Article 55 and Article 56 of Law Number 37 of 2004 prioritizes the interests of separatist creditors without having to go through aanmaning in court, the meaning of the debtor's insolvency should be an examination in court or through aanmaning regarding the debtor's ability to pay off his debts, not solely based on the analysis and views of separatist creditors. This is clearly implicitly based on Article 28D of the 1945 Constitution of the Republic of Indonesia and automatically contradicts the values of Pancasila social justice. Keywords: Creditor; Debtor; Execution; Legal; Protection.